KAMPANYE BLACK LIVES MATTER GLOBAL NETWORK FOUNDATION (BLMGNF) DALAM MENGATASI DISKRIMINASI RASISME DI KANADA 2020-2022 - Nugraha, Aditya; Nizmi, Yusnarida Eka (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Black Lives Matter Global Network Foundation is an organization that calls for the rejection of violence against black people and was formed based on the movement of the same name, namely Black Lives Matter. In 2020, this movement became global after the death of George Floyd at the hands of a police officer. In 2014, Canada became the first country outside the United States to sympathize with this event and also called for Black Lives Matter. For black people in Canada, they often experience racist discrimination, although not the same as in the United States. However, racism is a problem that they often face as a minority. This study aims to analyze how the Black Lives Matter Global Network Foundation campaign addresses racist discrimination in Canada. This study uses Social Movement theory and group analysis levels to examine the changes created by the BLMGNF organization. Social Movement Theory itself is the main vehicle for ordinary people to be able to participate in the political sphere that intersects with the people. The method used is a qualitative method that is a literature study by using and analyzing data through sources such as books, news, magazines, articles, journals and websites. The results of this study indicate that the role and efforts of BLMGNF are able to reduce racism against black people in Canada. The awareness and sense of humanity of the community towards this problem has moved to a better path where there were demonstrations carried out by thousands of people in Toronto, Vancouver, Montreal, Ottawa, and Calgary to demand justice for cases of discrimination. Keyword: Black Lives Matter, Canada, Racism